Une “ annexe ” agraire gallo-romaine à Saran “ les Cent Arpents ” (Loiret) - Aurélien Hamel; Alix Fourré (Revue Archéologique du Centre de la France)
Located 400 m east of the Roman road from Chartres-Autricum to Orléans-Cenabum, the site “les Cent Arpents” in Saran (Loiret) is made up of a small excavated enclosure covering a restored/estimated area of about 900 m², including a pond whose very likely/probable function is that of a drinking trough or a scrapper for the livestock. Immediately to the west of this enclosure, some ten meters away, a few structures are organized: at least one construction on poles whose interpretation is difficult, and two pits. The ceramic material indicates that this rural establishment was occupied since the second half of the 2nd century a.d., and abandoned during the 3rd century a.d. A possible close tile-making workshop can be associated with it.